2012
DOI: 10.1016/j.cub.2012.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Dachsous-Fat Planar Cell Polarity

Abstract: SUMMARY The Fat pathway controls both planar cell polarity (PCP) and organ growth [1, 2]. Fat signaling is regulated by the graded expression of the Fat ligand Dachsous (Ds), and the cadherin-domain kinase Four-jointed (Fj). The vectors of these gradients influence PCP [1], whereas their slope can influence growth [3, 4]. The Fj and Ds gradients direct the polarized membrane localization of the myosin Dachs, which is a crucial downstream component of Fat signaling [5–7]. Here we show that re-polarization of Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
168
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(184 citation statements)
references
References 25 publications
14
168
0
2
Order By: Relevance
“…It is planar polarized in the wing disc at the junction level, with one side of each cell-cell junction containing more Dachs, along a proximo-distal gradient (Fig. 3A, left-hand schematic) (Ambegaonkar et al, 2012;Mao et al, 2006;Schwank et al, 2011b). Dachs has also been proposed to be polarized in the wing disc at the cellular level, with tangent junctions being enriched compared with radial junctions, leading to a radial bias in cell shape (Fig.…”
Section: The Stress Pattern Is Independent Of Dachsmediated Planar Pomentioning
confidence: 99%
See 1 more Smart Citation
“…It is planar polarized in the wing disc at the junction level, with one side of each cell-cell junction containing more Dachs, along a proximo-distal gradient (Fig. 3A, left-hand schematic) (Ambegaonkar et al, 2012;Mao et al, 2006;Schwank et al, 2011b). Dachs has also been proposed to be polarized in the wing disc at the cellular level, with tangent junctions being enriched compared with radial junctions, leading to a radial bias in cell shape (Fig.…”
Section: The Stress Pattern Is Independent Of Dachsmediated Planar Pomentioning
confidence: 99%
“…There is significant evidence for the activity of Dachs to be polarized. It was shown that, at the singlejunction level, Dachs enriches one side more than the other along a distal-to-proximal gradient (Ambegaonkar et al, 2012;Mao et al, 2006;Schwank et al, 2011a). Our observations were not designed to resolve such a polarity (we could not resolve individual sides of a junction).…”
Section: The Origin Of Mechanical Stressmentioning
confidence: 99%
“…Cells in the eye become polarised through preferential distribution of the cadherin Ds (A*) to one cell end and its binding partner the cadherin Ft (B*) to the opposite cell end (Ambegaonkar et al, 2012;Brittle et al, 2012). Planar polarity patterns are specified by opposite gradients in expression of Ds and the Golgi-associated protein Four-jointed (Fj) (Simon, 2004).…”
Section: Hypothesismentioning
confidence: 99%
“…We confirmed by Western blot the expression of DsIntra protein. Similar levels of DsIntra were observed in wt and DsFL expressing cells, which rules out the possibility that DsIntra is a peptide deriving from proteolytic cleavage of DsFL, as has been suggested to explain the existence of small bands detected by a Ds antibody [26].…”
Section: Discussionmentioning
confidence: 79%